Increased Soil Carbon and Nitrogen Stocks Associate With Stronger Calcium–Microbial and Multi‐Trophic Interactions Under Warming - Dan Xiao; Wei Zhang; David R. Johnson; Peilei Hu; Lin Xu; Mingming Sun; Li Tang; Xunyang He; Jie Zhao; Xionghui Liao; Wanxia Peng; Hongsong Chen; et al. (Global Change Biology, 2026)
Converting cropland to planted forests improves soil organic carbon (SOC) and total nitrogen (TN) storage while contributing to climate change mitigation, primarily through the regulation of belowground organisms and mineral protection such as calcium (Ca). However, the mechanistic pathways linking exchangeable Ca 2+ , soil micro‐food web interactions, and nutrient accumulation under warming remain unclear. Here, we investigated their potential roles in driving the accumulation of mineral‐associated organic matter (MAOM), SOC, and TN in planted forests compared with croplands under warming conditions. Planted forests exhibited higher MAOM, SOC, and TN than cropland and had stronger coupling between carbon and nitrogen. Warming increased MAOM, SOC, and TN in planted forests but reduced SOC in cropland. Compared to cropland, planted forests displayed elevated levels of soil exchangeable Ca 2+ , microbial necromass carbon and nitrogen, stronger Ca–microbial and multi‐trophic associations. Warming further amplified positive Ca–microbial (e.g., bacteria and fungi) and cross‐trophic associations (e.g., nematode–bacteria, nematode–fungi, nematode–protist, and omnivore‐predator–bacteria/fungi) in planted forests by increasing plant productivity, litter biomass, and soil exchangeable Ca 2+ , whereas cropland showed limited responsiveness to temperature changes. In planted forests, soil exchangeable Ca 2+ was positively correlated with Ca–microbial and cross‐trophic associations, microbial necromass carbon and nitrogen, and the contents of MAOM, SOC, and TN. These relationships were absent in cropland. Notably, cross‐trophic associations rather than microbial abundance or diversity, with significant modulation by soil exchangeable Ca 2+ , had the strongest positive relationship with MAOM, SOC, and TN accumulation in planted forests. Collectively, our findings lead to the hypothesis that warming promotes SOC and TN storage in planted forests by jointly strengthening exchangeable Ca 2+ , Ca–microbial and cross‐trophic interactions. These results highlight the potential importance of multi‐trophic interactions and Ca‐mediated processes in stabilizing microbial necromass and fostering carbon and nitrogen preservation during vegetation restoration in response to warming.